2008
DOI: 10.1152/japplphysiol.00824.2007
|View full text |Cite
|
Sign up to set email alerts
|

Hyperventilation evoked by activation of the vicinity of the caudal inferior olivary nucleus depends on the fastigial nucleus in anesthetized rats

Abstract: Zhuang J, Xu F, Frazier DT. Hyperventilation evoked by activation of the vicinity of the caudal inferior olivary nucleus depends on the fastigial nucleus in anesthetized rats. J Appl Physiol 104: 1351-1358, 2008. First published March 20, 2008 doi:10.1152 doi:10. /japplphysiol.00824.2007eral studies have demonstrated that cerebellar deep nuclei, particularly the rostral fastigial nucleus (FNr), are involved in respiratory modulation. These nuclei receive inputs from the contralateral caudal inferior olivary n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Alterations in GABA neurotransmitter signaling may affect the respiratory control centers in the brainstem and induce stress breathing responses commanded by neurons located in the cerebellar deep nuclei, thus influencing the ventilatory response of the body [61]. Indeed, Purkinje cells may play a general role in the modulation of respiration in consequence of their projections to the fastigial nucleus [62].…”
Section: Resultsmentioning
confidence: 99%
“…Alterations in GABA neurotransmitter signaling may affect the respiratory control centers in the brainstem and induce stress breathing responses commanded by neurons located in the cerebellar deep nuclei, thus influencing the ventilatory response of the body [61]. Indeed, Purkinje cells may play a general role in the modulation of respiration in consequence of their projections to the fastigial nucleus [62].…”
Section: Resultsmentioning
confidence: 99%
“…The ION, the sole source of climbing fibers to the Purkinje cells, is known to receive cholinergic input from mesopontine ACh neurons (Woolf and Butcher, 1989), and is critical for somatic motor, respiratory, and autonomic coordination (Urbano et al, 2006; Zhuang et al, 2008). The specific role of nAChRs in the human infant ION is unknown, but their heavy concentration at this site likely increases the susceptibility of this nucleus to nicotine neurotoxicity at least through infancy.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, conveys cortical fibers via the pons to the cerebellum (cortico-ponto-cerebellar tract). Cerebellum was considered as an organ related to motor functions, however studies have shown its relations with cardiovascular, respiratory, gastrointestinal functions, further, cognition, working memory, emotion, reading skills and even with immune system [2,8,10,28,29,33,35,36]. Further, studies have shown the involvement of cerebellum in cognitive processes, such as processing and coordinating information [22].…”
Section: Introductionmentioning
confidence: 99%